Determinants Of Insurance Literacy, Brand Awareness And Price On The Interest In Purchasing Personal Accident Insurance At PT Askrindo (Persero) Case Study Bandung Branch - Gilang Satria Putra; Irma Nilasari (UNIVED Press, 2026)
Insurance penetration in Indonesia is still relatively low, with an insurance penetration rate of only 2.72% in February 2025. One of the insurance products that has seen a decline in purchasing interest is the Personal Accident Insurance from PT Askrindo Bandung Branch. Based on the preliminary survey results, only 5% of respondents have Personal Accident Insurance, while most prefer health insurance products. This study aims to analyze the influence of insurance literacy, brand awareness, and premium prices on the purchasing interest in Personal Accident Insurance products from PT Askrindo Bandung Branch.The research method used is quantitative with a descriptive and verificative approach, utilizing regression and correlation analysis. Primary data was collected through questionnaires distributed to 120 respondents aged 18-30 who have insurance products. The results of the study show that, simultaneously, insurance literacy, brand awareness, and premium prices significantly influence purchasing interest in Personal Accident Insurance products from PT Askrindo Bandung Branch, with a contribution of 64.2%. However, in partial analysis, insurance literacy was found to have no significant effect on purchasing interest, while brand awareness and premium price have a positive and significant impact.The conclusion of this study is that, to increase purchasing interest in Personal Accident Insurance products from PT Askrindo Bandung Branch, the company needs to focus on enhancing brand awareness and price competitiveness with its competitors. Promotional programs, advertising, and market access expansion can be effective strategies to increase public interest in purchasing these insurance products.